Effect of Anode Flow Channel Depth on the Performance of Polymer Electrolyte Membrane Water Electrolyser. (19th June 2018) - Majasan, Jude Olaoluwa; Cho, Jason I. S.; Maier, Maximilian; Dedigama, Ishanka; Shearing, Paul R.; Brett, Daniel J.L.
Abstract : This study investigates the influence of anode flow channel depth on the performance of a polymer electrolyte membrane water electrolyser (PEMWE). The channel depth was varied from 3 to 8 mm and the cell performance was studied at current densities up to 2.0 A cm -2 using electrochemical impedance spectroscopy (EIS). The effect of flow channel depth on performance was negligible at low and medium current densities, but significant at high current densities. Results show a non-monotonic dependence of channel depth on performance at high current density which was attributed to the coupled effect of flow velocity and mass transfer characteristics. Optimization of the dimensions and shape of the flow-field is crucial to reduce mass transport losses and improve electrolyser performance especially at high current densities.